The Role of RIPPDA in Sustainable Tourism Destination Management in West Sumatra: A Case Study of Tourism Policy - Belly Rozano; Retnaningtyas Susanti; Yuliana Yuliana; Feri Ferdian (Dinasti Publisher, 2026)
Tourism is one of the strategic economic sectors in West Sumatra Province, yet its development continues to face challenges in sustainable destination management. This study aims to analyze the role of the Regional Tourism Development Master Plan of West Sumatra Province in managing tourism policies. The research object is tourism policy management in West Sumatra Province. This study employed a qualitative approach through document analysis and interviews, with the researcher acting as the main instrument. The findings indicate that the Regional Tourism Development Master Plan has formulated policies focused on environmentally friendly infrastructure development, culture-based tourism, and community empowerment. However, policy implementation still encounters obstacles, including weak coordination among government institutions, limited budget allocation, and low community participation. Despite these challenges, the Regional Tourism Development Master Plan has substantial potential to support sustainable tourism management if implemented effectively. Therefore, strong synergy among government stakeholders and a high level of commitment are essential to optimize tourism policy management and ensure sustainable tourism development in West Sumatra Province